Gemah Ripah: Gerakan Masyarakat Hidup Bersih dan Produktif dari Rumah di Desa Cendana - Syafitri Hidayati; Argo Condro Pralampito; Annisa Prabaningrum; Andika Yudi Zahidah; Pradyta Galuh Oktafiani (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
New normal is a government policy that must be implemented in everyday life, including in the life of the people on Cendana Village, Banjarnegara Sub-District, Banjarnegara Regency, Central Java. The spread of COVID-19 has also affected various sectors of social life from economy, politics, social, and culture. This activity aims at public awareness to apply the new normal protocol, support the food needs of the community during pandemic by utilizing residents yard, and increase the selling value of the crops produced by residents with simple innovations from home. This activity was carried out on 8-18 August 2020. The results obtained were an increase in knowledge of COVID-19 and the application of a new normal protocol based on the results of the pre-test and post-test, the formulation of the “Lintang Asri” Farmer Woman Group at Dukuh Lintang Tiba, Cendana Village, 37and the direct application of the knowledge obtained after the socialization and demonstration of agriculture product innovation by several residents in Cendana Village. Keywords: community movement, yields, yard